2017
DOI: 10.1159/000464468
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Obscuration in Retinoblastoma: A Risk Factor for Optic Nerve Invasion

Abstract: Background: The objective of this study is to evaluate the risk of optic nerve invasion associated with optic nerve obscuration at diagnosis or persisting during treatment. Methods: Retrospective review from 2011-2016 of patients with advanced retinoblastoma (Group D/E) with complete obscuration of the nerve at diagnosis and a second group of patients with persistent, complete obscuration throughout treatment. Results: Advanced retinoblastoma was diagnosed in 102 eyes of 86 patients. The optic nerve was obscur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Studies have shown that cases with massive choroidal invasion are more likely to develop metastasis 21 . Similar to our study, Berry et al too reported that optic nerve (RL+CE) invasion has the highest prediction ability for metastasis and mortality rate 22 . Our observation is similar to the study of Mendoza and coworkers in which they found statistically significant correlation between optic nerve (RL+CE) invasion and metastasis 23 …”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that cases with massive choroidal invasion are more likely to develop metastasis 21 . Similar to our study, Berry et al too reported that optic nerve (RL+CE) invasion has the highest prediction ability for metastasis and mortality rate 22 . Our observation is similar to the study of Mendoza and coworkers in which they found statistically significant correlation between optic nerve (RL+CE) invasion and metastasis 23 …”
Section: Discussionsupporting
confidence: 91%
“…Much higher cases with optic nerve invasion of 33.2% and 69.7% have been reported by Mukhtar and coworkers [25] in Uganda and Owoeye et al [23] in Nigeria, respectively. Optic nerve invasion appears to predict metastasis and mortality rate especially when the extent of invasion is considered [34]. Optic nerve involvement is found in 25%–45%; however, its risk on outcome appears to be limited to the involvement beyond the lamina cribrosa and to the optic nerve surgical margin [34].…”
Section: Discussionmentioning
confidence: 99%
“…Optic nerve invasion appears to predict metastasis and mortality rate especially when the extent of invasion is considered [34]. Optic nerve involvement is found in 25%–45%; however, its risk on outcome appears to be limited to the involvement beyond the lamina cribrosa and to the optic nerve surgical margin [34]. When the extent of optic nerve invasion was not considered and association with metastasis was done in this study, it was found that there was no association with metastasis ( P = 0.39) although the trend of cases with optic nerve invasion to develop metastasis was higher than the ones without optic nerve invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The Choroidal invasion has also been shown to correlate with molecular prognostic markers such as TP53, in contrast to other high-risk factors. Optic nerve invasion appears to predict metastasis and mortality, especially when the extent of invasion is taken into account [ 2 , 21 ]. Optic nerve involvement in our series was found in 27.9%; a rate similar to the 25% reported by Chebbi et al.…”
Section: Discussionmentioning
confidence: 99%